CONTEMPORARY PROBLEMS OF EVALUATION OF HYPERTENSION TREATMENT EFFICACY: MASKED HYPERTENSION AND WHITE COAT HYPERTENSION - V. M. Gorbunov; M. I. Smirnovа (Рациональная фармакотерапия в кардиологии)
The implementation of contemporary ambulatory methods of BP level evaluation in clinical practice improved diagnostics of arterial hypertension (HT), but at the same time faced with specific problems. White coat HT (WCHT) and masked HT are characterized by inconsistency between ambulatory and clinical BP levels. Studying of these conditions in patients receiving antihypertensive therapy is important. The WCHT during treatment (target ambulatory BP levels and no control of clinical BP) is observed in 10-20% of patients. The cardiovascular risk in these patients does not differ significantly from the risk in patients with controlled BP. Masked HT (target levels of clinical BP and no control of ambulatory BP) is observed in 5,4-23% of patients. The cardiovascular risk in patients with masked HT is 2,5-3,0 times more than that in patients with controlled HT and comparable with risk in patients with ineffective antihypertensive therapy. Thus, clinical measurements can give inexact data about true BP level in one third of treated hypertensive patients. Therefore the evaluation of cardiovascular risk and correct usage of ambulatory BP measurement is important for choice of therapy tactics in patients with HT.